Caracterização de Escherichia coli isoladas de perus - Hoepers, Patrícia Giovana (2016)
Avian Pathogenic Escherichia coli (APEC) are part of the class of ExPEC (Extra intestinal Escherichia coli). APEC cause localized or systemic disease in poultry production termed avian colibacillosis. Turkeys, unlike broilers have a long life and are therefore more susceptible to onset of diseases, respiratory and septicemic disease caused by E. coli. Advances in genotyping and sequencing have shown similarities of APEC isolates with human ExPEC, bringing up the possibility of these isolates play a role on public health as pathogens or as virulence genes reservoirs. Antimicrobial resistance in human communities caused by multidrug resistant E.coli is also a huge concern. Many authors have done the characterization of E. coli isolated from poultry. In Brazil, recent publications characterized the virulence and antimicrobial resistance of E. coli isolated from cellulitis lesions in broilers and air sacs affected by aerosacculitis in turkeys. However, no study was carried out considering samples of the main producing States and the production of beta-lactamases, ESBL (extended spectrum beta- lactamase) and pAmpC (plasmid-mediated cefalosporinases) in the isolates. The aim of this study was to characterize isolates of E. coli in turkeys organs suspected of colibacillosis for five genes associated with plasmid CoIV, access the antimicrobial resistance in important antimicrobials for poultry and human health and check the presence of genes for beta- lactamase, ESBL, pAmpC and phylogenetic classification E. coli with the resistance phenotype for ceftiofur and amoxicillin. The results showed that 84.3% of the isolates harbored four or five genes being characterized as APEC, the selected isolates for phylogenetic classification belong mainly to groups B1 and D. In total, 82.14% of isolates were considered MDR (multidrug resistant to antimicrobials); higher resistance indices were to erythromycin (99%) and amoxicillin (76.1%). The 43 isolates resistant or intermediate to ceftiofur on antibiogram were positive for ESBL or pAmpC. ESBL genes associated were 79.4% blaCTX-M-2 and 20.59% blaCTX-M-8 /25. Nine isolates that were positive for pAmpC were blaCMY II. The state of Goiás was responsible for most of the isolates resistant to ceftiofur and was the only where blaCMY-II genes have been identified. This study demonstrates the high prevalence of APEC in suspected cases of colibacillosis in turkeys, high antimicrobial resistance index and alert for resistance to ceftiofur and the presence of E. coli ESBL and pAmpC in the production chain of turkeys.